Wheat floral biology: prospects for improving the efficiency of hybrid seed production and abiotic stress tolerance - John-Bejai, Carus Kristoff Joel (2018)
The modification of floral characteristics will be beneficial in improving the efficiency of hybrid seed production and the breeding of more climate resilient varieties in bread wheat (Triticum aestivum). Methods for phenotyping floral traits were initially tested using small genotype panels under controlled conditions and in field trials. Low-tech phenotyping methods appropriate for use by breeders and researchers were developed and demonstrated to be accurate. A panel of 111 genotypes was subsequently assessed in field trials using these methods. A high level of genotypic variation was observed for anther extrusion, anther length and anthesis duration/pattern and phenotypes were found to be stable across trials. Using this phenotypic data set, floral trait marker-trait associations (MTAs) were detected by association mapping and additional anther extrusion quantitative trait loci (QTLs) have been detected by linkage mapping in a bi-parental population. The phenotypic effects of candidate loci co-localizing with MTAs and QTLs were investigated using TILLING mutants and modifications to floral characteristics have been observed in some mutant lines. The utilization of phenotyping and genomic resources described in the present study is discussed and areas of future research have been identified.